CHRONOBIOLOGICAL ASPECTS OF CIRCADIAN RHYTHMS - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The internal clock of human is functioning in the absence of external signals. The system operates through the influence of luminosity on to melapsyn receptors of the retina, which transmits information on to suprahiazmatych nucleus, where signals must be send in the endocrine glands that through the hormones regulate circadian rhythm. Circadian rhythms are used in science as a universal criterion for assessing human health. Each organ has its own healing activity and its healing time. Light absorption and excretion of drugs depends on circadian rhythms. On base of this the optimal time of taking different medicine and preventing crises is founded.